BREASTFEEDING AND WEANING UNDER WAR AND SIEGE: MOTHERS’ KNOWLEDGE, PRACTICES AND BARRIERS IN GAZA STRIP - Aymen Elsous; Eman Alhawajri; Ezat Askari; Seham Abu Shawish; Raghad Samour; Hadeel Hooso (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Breastfeeding is a critical lifesaving intervention in conflict settings like the Gaza Strip. This study assessed mothers' adherence to breastfeeding and weaning practices during wartime and identified barriers to optimal infant feeding.   Method: A descriptive cross-sectional design was adopted, targeting 200 mothers attending maternal and child health centers in the middle area of Gaza from July to Sept, 2025. Convenient sampling was approached and data were collected through structured questionnaires. The SPSS software was used for analysis.   Result: Majority of mothers (84.5%) initiated breastfeeding immediately after birth. Only 29.5% adhered to exclusive breastfeeding during the first six months, and 82.1% continued breastfeeding after six months in combination with complementary feeding. Around 70% of mothers reported using alternative feeding, mostly formula milk (76.1%). Barriers to breastfeeding included food shortages (50.4%), psychological stress (30.7%), and lack of breastfeeding support (56.5%).   Conclusion: Most mothers initiated breastfeeding, but adherence to exclusive breastfeeding during the first six months is considerably low. Many mothers resorted to alternative feeding methods, particularly formula milk, due to the compounded challenges of wartime conditions. A significant gap between maternal knowledge of recommended practices and the harsh realities of war is observed. It is highly need to strengthen the role of health personnel on exclusive breastfeeding support strategies, and to enhance psychosocial and nutritional support for breastfeeding mothers during wars. Also, to emphasize the importance of implementing WHO and UNICEF standards in regulating the distribution of formula milk and limiting its use to documented medical conditions.             Keywords: Breast-feeding, Weaning, Alternatives feeding, Knowledge, Practices, Perception